2014
DOI: 10.1177/0148607114542515
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Providing a Combination Lipid Emulsion Compared With a Standard Soybean Oil Lipid Emulsion in Children Receiving Parenteral Nutrition

Abstract: There is inadequate evidence that combination lipid emulsions offer any benefit regarding bilirubin levels, triglyceride levels, or incidence of infection compared with soybean oil lipid emulsions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 52 publications
(291 reference statements)
2
14
0
3
Order By: Relevance
“…This systematic review is the first to fully explore the effects that various LEs have on a comprehensive range of growth, development, laboratory and clinical outcomes in paediatric patients ranging from preterm infants to children < years of age. The majority of studies did not find significant differences between the use of different LEs and growth, liver enzymes, plasma triglycerides, oxidative stress, blood parameters and inflammatory markers, which is consistent with the findings of four previous systematic reviews investigating the safety and possible beneficial effects of different LEs in preterm infants (n=3) and children (n=1) [8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…This systematic review is the first to fully explore the effects that various LEs have on a comprehensive range of growth, development, laboratory and clinical outcomes in paediatric patients ranging from preterm infants to children < years of age. The majority of studies did not find significant differences between the use of different LEs and growth, liver enzymes, plasma triglycerides, oxidative stress, blood parameters and inflammatory markers, which is consistent with the findings of four previous systematic reviews investigating the safety and possible beneficial effects of different LEs in preterm infants (n=3) and children (n=1) [8][9][10][11].…”
Section: Discussionsupporting
confidence: 88%
“…Two studies also showed a potential benefit of fish oil-containing blends on lowering the risk of ROP [31,45]. ROP was not an investigated outcome in three of the earlier systematic reviews [9][10][11] whilst the review of Vlaardingerbroek et al [8] predates both relevant studies [31,45]. Fish oil contains significant amounts of both EPA and DHA and the abundance of DHA in fish oil is likely to be responsible for the beneficial effect on ROP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in agreement with several studies in the literature. Multiple trials and meta-analyses, including several in IF populations have shown that the use of a combination lipid emulsion decreases bilirubin levels more effectively than soybean-based emulsions, thereby treating cholestasis [24][25][26][27]. Similarly, in 2010, a randomized controlled trial in infants and children with intestinal disease and early signs of liver injury demonstrated a decrease in markers of cholestasis in those patients receiving SMOF over a 4-week period compared to patients receiving soybean emulsion [28].…”
Section: Discussionmentioning
confidence: 99%
“…En RNPT se obtuvo una significativa reducción de bilirrubina total y directa junto con un equilibrio en la proporción de AGE en los tratados con SMOFlipid ® frente a los que recibieron Intralipid ® (33). Estos beneficios en los niveles de bilirrubina, así como en los de triglicéridos e incidencia de infección, no se han confirmado en un metaanálisis posterior (34). Otros metaanálisis no han podido demostrar en el RN el efecto protector del aceite de pescado frente a la enfermedad hepática relacionada con la NP (35) ni pruebas suficientes para recomendar ninguna solución lipídica mixta sobre las convencionales a base de aceite puro de soja o viceversa sugiriendo la necesidad de estudios adicionales, aunque se haya observado una pequeña reducción de la retinopatía del prematuro y de la displasia broncopulmonar en los tratados con la fórmula SMOFlipid ® (36).…”
Section: Requerimientos De Lípidosunclassified